2019
DOI: 10.20944/preprints201901.0154.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple Method of Creating Hydrophobic Surfaces Based on Modified MW-CNTs

Abstract: The creation of hydrophobic, antifreeze and self-cleaning coatings is currently being pursued by many industrial sectors. The potential applications include the production of liquid and gas separators and filters, new materials, optical and microelectronic devices, and textiles and clothing. These coatings will also have wide application in the construction and automobile industries, shipping, and energy and agricultural sectors. The article proposes a simple approach to the creation of superhydrophobic and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Thus, they obtained a material with a contact angle of almost 151 • and concluded that the short functionalization periods of MWCNTs (up to 90 min) are dominated by the cleaning process of the nanotubes (amorphous carbon and metal nanoparticles-the catalyst). The MWCNTs functionalized for 90 min showed an increase in the contact angle from 112 • (value obtained for a working time below 90 min) to 140 • (90 min operating time), allowing this coating to be considered as being highly hydrophobic [164]. In a recent study, MWCNTs were synthesized by catalytic CVD, and on the surface of these nanotubes was physically adsorbed fluid poly (dimethylsiloxane) fluid, in order to obtain a superhydrophobic nanocomposite material.…”
Section: Properties Of Cnts Important For Cultural Heritagementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they obtained a material with a contact angle of almost 151 • and concluded that the short functionalization periods of MWCNTs (up to 90 min) are dominated by the cleaning process of the nanotubes (amorphous carbon and metal nanoparticles-the catalyst). The MWCNTs functionalized for 90 min showed an increase in the contact angle from 112 • (value obtained for a working time below 90 min) to 140 • (90 min operating time), allowing this coating to be considered as being highly hydrophobic [164]. In a recent study, MWCNTs were synthesized by catalytic CVD, and on the surface of these nanotubes was physically adsorbed fluid poly (dimethylsiloxane) fluid, in order to obtain a superhydrophobic nanocomposite material.…”
Section: Properties Of Cnts Important For Cultural Heritagementioning
confidence: 99%
“…Presently, the aim is to create hydrophobic, anti-freeze and self-cleaning coatings in several industrial sectors, particularly in the cultural heritage area. These coatings will also have a wide application in the construction and automotive industries [164]. To date, only a few studies have been reported on heritage conservation by using CNTs, which have been very successful in the consolidation and restoration of the object [167,168].…”
Section: Cnts Used In Conservation and Restoration Of Cultural Heritage And Future Challenges In This Areamentioning
confidence: 99%
“…However, VACNT forest in their pristine form deprived of the accessible specific surface area due to their vertically stacked orientation and non-polar behavior [9]. But oxidation of these aligned structures helps in the incorporation of oxygenated functional groups along with the formation of CNT bundles [10]. Consequently, the oxygenated functional groups and the open porous structure of the hybrid electrode thus formed, increases the number of interaction sites available for the electrolyte ions.…”
Section: Introductionmentioning
confidence: 99%